2022
DOI: 10.1111/1751-7915.14072
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing fluxes through the mevalonate pathway in Saccharomyces cerevisiae by engineering the HMGR and β‐alanine metabolism

Abstract: Mevalonate (MVA) pathway is the core for terpene and sterol biosynthesis, whose metabolic flux influences the synthesis efficiency of such compounds. Saccharomyces cerevisiae is an attractive chassis for the native active MVA pathway. Here, the truncated form of Enterococcus faecalis MvaE with only 3-Hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) activity was found to be the most effective enzyme for MVA pathway flux using squalene as the metabolic marker, resulting in 431-fold and 9-fold increases of sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…Similarly, mitochondria have nearly 20-30 times higher acetyl-CoA content than the cytosol (Duran et al, 2020). As shown in Figure 2C, rational organelle compartmentalization can greatly improve the utilization efficiency of the acetyl-CoA pools in different organelles (Son et al, 2022a;Lu et al, 2022). Dong et al (2021) compartmentalized the whole MVA pathway into mitochondria, leading to a 3.7-fold improvement in the production of α-santalene.…”
Section: Monoterpenoids and Sesquiterpenoidsmentioning
confidence: 94%
“…Similarly, mitochondria have nearly 20-30 times higher acetyl-CoA content than the cytosol (Duran et al, 2020). As shown in Figure 2C, rational organelle compartmentalization can greatly improve the utilization efficiency of the acetyl-CoA pools in different organelles (Son et al, 2022a;Lu et al, 2022). Dong et al (2021) compartmentalized the whole MVA pathway into mitochondria, leading to a 3.7-fold improvement in the production of α-santalene.…”
Section: Monoterpenoids and Sesquiterpenoidsmentioning
confidence: 94%
“…On the other hand, yeast and bacteria use NADH more than NADPH as a reduced cofactor of catabolism [ 4 ]. Thus, increasing the intracellular NADPH level or eliminating NADPH consumption is a common strategy to facilitate NADPH-dependent products, including terpenoid [ 14 , 15 ]. For example, Liu et al compared the effects of six native enzymes involved in NAPDH regeneration in Yarrowia lipolytica and found that mannitol dehydrogenase benefits the increase in squalene production [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, dosedependent regulation of gene expression will help to optimize flux through a pathway by adjusting the endogenous gene expression levels flexibly and in a cloning free manner. The fact that the adjustment of endogenous protein levels has a positive influence on product yield has already been described several times, e.g., for terpene production, 19 overproduction of Design of sgRNA Entry and Multimerization Vectors. The expression of sgRNAs is based on the previously published tRNA-HDV architecture, 23 which we modified to allow Golden Gate-based cloning of up to four sgRNA cassettes into a single plasmid (see Figure 2 and the Methods section for details).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Further, dose-dependent regulation of gene expression will help to optimize flux through a pathway by adjusting the endogenous gene expression levels flexibly and in a cloning free manner. The fact that the adjustment of endogenous protein levels has a positive influence on product yield has already been described several times, e.g., for terpene production, overproduction of triacylglycerols (TAGs), , and high-level production of aromatic chemicals …”
Section: Introductionmentioning
confidence: 99%